Low utility of blood culture in pediatric community-acquired pneumonia: An observational study on 2705 patients admitted to the emergency department. Issue 22 (June 2017) - Kwon, Jae Hyun; Kim, Jung Heon; Lee, Jeong-Yong; Kim, Youn-Jung; Sohn, Chang Hwan; Lim, Kyoung Soo; Kim, Won Young
Abstract : Abstract: To investigate the utility of blood cultures performed on previously healthy children and adolescents with community-acquired pneumonia (CAP) at a tertiary care hospital emergency department (ED). We reviewed 3235 patients with CAP aged 6 months to 18 years who underwent blood cultures at the ED from 2009 through 2016. CAP was defined according to the International Classification of Diseases, 10th Revision codes for pneumonia and the requirement of antibiotic treatment plus any of the following: radiologically confirmed, hospitalized, or moderate to severe disease. Blood cultures were retrospectively justified by the Infectious Diseases Society of America guidelines. We measured the yield (true positive results of blood culture) and impact (blood culture-directed change in the antibiotic regimen). Of 2705 previously healthy patients with CAP, 833 (30.8%; 95% confidence interval [CI]: 29.1–32.6) underwent blood cultures justified by the current guidelines. We found 12 patients (0.4%; 95% CI: 0.2–0.8) having positive results of blood culture, 7 of whom underwent justified blood cultures. Of these 7 patients, 3 (0.11%; 95% CI: 0.02–0.3) had the yield, Streptococcus pneumoniae . No impact was made in these 3 patients with S pneumoniae . We confirmed a low utility of blood cultures in previously healthy children and adolescents with CAP who were admitted to the ED. This finding suggests the need to refine the current guidelines for obtaining blood cultures in the ED for pediatric CAP. Abstract : Supplemental Digital Content is available in the text